Dealing with the Allegedly Impossible: a pedagogical action research investigation into teaching and learning the translation of cultural items - Mundt, Klaus (2023)
The translation of cultural items is a contested area of high difficulty that is prone to problematisation and allegations of impossibility in parts of the literature. Learner psychology suggests that a positive mind set correlates with learner engagement and can also positively affect attainment (Canfora 2013; Ghaye 2011). Thus, pedagogy needs to be supportive (as opposed to problem-oriented) to encourage learners to engage with great challenges, such as the translation of cultural items. Holistic research on translator education, especially focussing on cultural items, is rare (Angelelli and Baer 2016; Gile 2004; Li, Zhang and He 2015), and this risks the use of pedagogical approaches without empirically testing how successful these really are. In that light, the present study undertook an action research project to test how successful a teaching approach informed by social-constructivist pedagogy and collaborative task-based learning is. An 8-session programme was designed and delivered to a cohort of MA Chinese-English Translation and Interpreting students to teach the translation of cultural items. Using a quasi-experimental setup and mixed methods, the study applied the Pedagogical Imperative cycle (Lantolf and Poehner 2014). It related its findings to established translation competence frameworks (Katan 2003; Kelly 2005; PACTE 2011; PICT 2012; Stolze 2015) and the notion of threshold concepts (Meyer and Land 2006a; 2006b). The results indicate that the programme was very well-received and significantly raised the participants’ confidence regarding translating cultural items. However, there was no statistically significant increase in student attainment. The participants would have required more time and practice to become increasingly self-sufficient and versatile. Katan’s and PICT’s competence Level 3 were approached but not consistently achieved. The data further yielded insights into translation choices that can facilitate or undermine the successful translation of cultural items. These raise questions about the helpfulness of common textbook advice. As part of the implications, this thesis makes concrete suggestions for teaching the translation of cultural items. It further suggests firmly integrating educational psychology into curricular development, specifically elements from Positive Psychology, Hope Theory and Mediated Learning Experience. This thesis cautions against the vilification of teaching as ‘transmissionist’ (e.g. Kiraly and Hofmann 2016). It suggests a bricolage approach to educational design that can help prevent getting trapped in restrictive paradigms. The thesis concludes that the translation of cultural items can indeed be taught and learned, but that this requires time, practice and a positive, solution-oriented learning environment. Its main contributions are that it undertook holistic research to empirically test common teaching approaches and make concrete suggestions for teaching the translation of cultural items. It further adds new perspectives on pedagogy that can help enrich translator education.